Non-Stationary Temperature Distribution and Thermoelectromotive Force for Optical Thermoelement at Anti-Parallel Directions of Temperature Gradient and Ray Current - Gutsul, I. V.; Gutsul, V. I. (Physics and Chemistry of Solid State, 2015)
The possibilities of utilization of anisotropic optical thermoelements (AOT) with different magnitudes of optical transparency for the registration and transformation of high-intensive ray currents are observed. The solution of non-stationary unhomogeneous equation of thermoconductivity is presented taking into account the Bouguer Lambert law at anti-parallel directions of ray current and temperature gradient for the anisotropic plate ZnAs2. It is shown that the non-stationary temperature distribution is determined by anisotropy of thermoconductivity and optical properties of thermoelement material and is characterized by complicated non-linear dependence both of coordinates and time. The expressions for the thermoelectromotive force are obtained for the case of optical transmitting and surface absorption. The dependences of transversal thermoelectromotive force on the time and height of thermoelement are investigated.